“Cet autre nécessité essentiel: l’urbanisation”. - Electrification and the Urbanisation of the Nebular City - Bruggeman, Dieter (International Planning History Society Proceedings, 2016)
Since the end of the nineteenth century, modern utility systems together with improved transport infrastructures and information technologies introduced new spatial arrangements and temporalities in the territory. The network based topology of these systems and infrastructures enabled logics of accumulation and distribution that, in time, attenuated the traditional town-country divide. As a result, the emergence and expansion of these systems reveal a notion of urbanization in which co-evolving processes lead to differentiated territorial arrangements. They show ways in which urbanization does not only takes place in or directly adjacent to the traditional (territorially bounded, mercantile) city. The Belgian ‘nebular city’ –the rhizomatic dispersion of population and activities across the Belgian territory– emerged out of the interplay of the multiple territorial arrangements resulting from these processes. The nation’s distributed urban condition is often explained by its historical roots in policies of industrial dispersal: Railroads, canals and highways were constructed in order to make the necessary resources such as land and labour accessible and this all over the country; Furthermore, labourers were encouraged to dwell in the countryside in order to keep wages low, to avoid major investments in means of collective consumption and to consolidate social power relations. In such a perspective, the nebular city becomes the product of industrial dispersal. Urbanization is assigned a secondary role only. In the accommodation and organisation of the territory, however, urbanization brings about the territorial and social context that guarantees the continuity of the industrialization process. In other words, the process of urbanization is crucial for the reproduction of the conditions in which industrialization can take place. This paper examines the extent to which Belgian urban planning engaged with the projects to establish the production and distribution of electricity. Although it is not one of their main drivers, the electrification is both intertwined with the rise of industrial production and the development of an urban modern lifestyle. Initially, little attention was paid to its spatial consequences. Only in the 1930’s, planners and designers explored issues such as the appropriate scale of the network or the economic opportunities shaped or squandered by equipping the entire country in a non-selective manner. More generally, the urban condition and society created by such strategies would become the subject of concern in magazine articles, academic papers or counterproposals. Standpoints towards electrification were rather ambiguous: electricity could be at the crux of an argument for a rigid, rationalist planning, but as well be described as one of the crucial amenities that underpinned the nebular city. The article takes a close look at two different projects (the highway project for Ghent of Jerome Desplanques and Gustave Magnel and the studies on Charleroi by Victor Bourgeois). Both projects are embedded within the international debate on the functional city and present Belgium as a particular case. They show the general delay and mismatch between the process of industrialisation and urbanisation because of the nation’s chosen development path, both in spatial and temporal terms.